Shopping Mall Revitalization as Experiential Transformation: A Mixed-Method Case Study of Mall Atmosphere and Visitor Experience - Pertiwi, Adeanna P; Sihombing, Antony (CSID Journal of Infrastructure Development, 2026)
Shopping malls are under growing pressure to stay relevant as e-commerce reshapes consumer behaviour and reduces foot traffic in physical retail environments. Although revitalization has become a common response, most studies evaluate it through physical outcomes alone, and the question of how spatial and atmospheric changes translate into shifts in visitor experience remains largely unaddressed. This study examined shopping mall revitalization as an experiential transformation, with the aim of understanding how physical and atmospheric changes shaped visitor experience at Lippo Mall Nusantara, South Jakarta. A mixed-method approach was used. The approach combined direct observation and photographic documentation with a questionnaire survey administered to 36 mall visitors. Mall experience was assessed across four dimensions: functional, recreational, social, and seductive. Physical observation identified several revitalization interventions, including the redistribution of food and beverage tenants across multiple floors, the introduction of nature-themed design elements at the mezzanine level, the addition of public seating and relaxation facilities, and improvements to the circulation system. These changes produced a more open, visually distinct, and socially active environment. Among the four experience dimensions, the recreational dimension recorded the highest mean score (5.60), followed by social (5.34), functional (4.74), and seductive (4.42). The recreational and social dimensions fell in the high category, although the functional and seductive dimensions remained at a moderate level. The dominance of recreational and social scores points to a clear shift in how visitors use and perceive the mall, as a destination for leisure and social activity with shopping as a secondary purpose. The lower seductive score suggests that the revitalization did not strongly stimulate impulse-driven purchasing behaviour, consistent with the experiential orientation of the spatial changes observed. This study contributes to the literature by demonstrating that the four-dimensional mall experience framework is sensitive to revitalization-induced changes, and that atmospheric and spatial design interventions produce measurable and differentiated effects across experience dimensions. For mall developers and urban retail planners, the findings suggest that revitalization strategies built around communal space, sensory design, and food and beverage programming are more effective at driving visitor engagement than those focused on commercial floor layout. Mall revitalization, when designed around experiential and social priorities, can meaningfully reposition a shopping mall within its urban retail context.